The deleterious impacts of dietary titanium dioxide nanoparticles on the intestinal microbiota, antioxidant enzymes, diseases resistances and immune response of Nile tilapia. (29th August 2021) - Sherif, Ahmed H.; El‐Sharawy, Mohamed El‐Sayed; El‐Samannoudy, Salma I.; Adel Seida, Ahmed; Sabry, Nader M.; Eldawoudy, Mohamed; Abdelsalam, Mohamed; Younis, Nehal A.
Abstract: Titanium dioxide nanoparticles (TiO2  NPs) are used in numerous products, such as paints, pharmaceuticals, environmental sanitizing agents and even as a whitening food additive (E171). Residual TiO2  NPs are considered among the emerging contaminants of aquatic environments. However, the effect of such exposure on intestinal microbiota population, microbial disease resistance and the immune‐related gene expression of Nile tilapia ( Oreochromis niloticus ) is largely obscure. Three groups of fish were nurtured on diets containing 1 mg/ml TiO2 NPs with three different sizes (53, 31 and 13 nm), beside the control group for four weeks before sampling fish tissues. Fish groups fed on TiO2 NPs diets showed significantly increased higher levels of tumour necrosis factor (TNF‐α), interleukin (IL‐6) and IL‐1β, along with insignificant changes in IL‐8 and IL‐10 compared with the control group. These changes indicate a strong inflammatory response. Treated fish groups showed a marked decrease in the count of some intestinal microbiota, aeromonas, pseudomonas and lactobacillus. Fish were challenged against A .  hydrophila, and a higher mortality rate was observed in the group fed on smaller TiO2  NPs (13 nm). The levels of antioxidant enzymes such as catalase, glutathione peroxidase and superoxide dismutase were significantly increased in groups fed on TiO2  NPs, while metallothionein levels were only slightly changed. In conclusion, feeding fish with diets containing TiO2  NPs (13 and 31 nm) for 4 weeks alters the intestinal microbiota population and provides additional information on the toxic impacts of TiO2  NPs on the health and immune status of O. niloticus .